Estimating the Ultimate Energy Dissipation Capacity of Steel Pipe Dampers. (2015) - Utomo, Junaedi; Moestopo, Muslinang; Surahman, Adang; Kusumastuti, Dyah
Abstract: Steel pipe damper specimen tests are very important but expensive and time consuming. Therefore efficient tools are needed to minimize the expense and the time by avoiding unnecessary or unneeded tests. This paper elaborates a practical component integrity assessment using finite element ductile fracture simulation based on local approach, and estimates the ultimate energy dissipation capacity of steel pipe dampers using energy based damage model. Ductile fracture in steel components that happens in fewer than twenty constant amplitude loading cycles is known as Ultra Low Cycle Fatigue (ULCF). Under ULCFs load steel pipe dampers experienced large scale cyclic yielding. Accurate preliminary prediction of ductile fracture is critical to estimate the performance of steel pipe dampers. The hysteretic behavior and ultimate energy dissipation capacity are investigated via finite element simulation after the component integrity assessment has been done. A micromechanics-based model which provide accurate criteria for predicting ductile fracture and an energy-based damage model to quantify the ultimate energy dissipation capacity of steel pipe dampers are applied. Using these approaches, ultimate energy dissipation capacity of steel pipe dampers can be estimated under various patterns of loadings. The approaches described here can also be applied to other steel dampers subjected to randomly flexural/shear stress reversals.